Composite trampoline metamaterial with enlarged local resonance bandgap. (15th December 2021) - Muhammad; Hussain, Sayed Iftikhar; Lim, C.W.
Graphical abstract: Highlights: Bulk elastic wave propagation through pillared-plate structural system is analyzed. Composite trampoline metamaterial is proposed to enlarge local resonance bandgap. Wave dispersion and frequency response studies are performed to study the dynamical characteristics. The effectiveness of composite pillar-plate system for low-frequency wave attenuation is established . Abstract: The engineered resonance phenomena by artificial structures have opened a new frontier in modern science and technology. Artificial structures such as pillared phononic crystals and metamaterials are emerging domain due to their surface resonance features that are governed by periodic array of pillars embedded on a host plate. The dual aspects of pillared structure exhibiting both Bragg and local resonance bandgaps make it a prominent choice for wave manipulation in general and vibration isolation in particular. The present study proposes pillared-plate structure based composite trampoline metamaterial that can exhibit ultrawide local resonance bandgap with relative bandwidth around 100%, confirmed by numerical and experimental approaches. The study establishes that composite nature of the pillar together with trampoline effect caused by drilling periodic array of holes in the host plate can enhances the effective mass density and reduce the plate stiffness, respectively that eventually lead to enlarged local resonance bandgap. The evolution of composite design with trampoline effect from parent pillar-plate structure is also fully discussed through wave dispersion and frequency response studies, and the widening of local resonance bandgap is demonstrated. By a parametric study, the effect of geometric parameters on the reported bandgaps is elaborated. Both numerical and experimental results validate the effectiveness of composite trampoline pillar-plate structure in attenuating bulk waves over broadband frequency spectrum. The new findings reported here provide another perspective on the dynamical characteristics and usefulness of pillared metamaterials for wave manipulation and subwavelength vibration attenuation.